Penetrating waterproofing coatings based on slag -containing cements, modified by natural zeolites - Пушкарева, Екатерина Константиновна; Суханевич, Марина Владимировна; Бондарь, Екатерина Владимировна (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with obtaining penetrating waterproofing coatings for concrete surfaces based on the slag-cement systems, modified by natural zeolite additives. The composition was investigated and physico-mechanical properties of slag-containing cements with natural zeolite, which were subsequently modified by the salt-electrolyte complex to create penetrating coating, were optimized. Studying the properties of the developed coating has confirmed its competitiveness in the market of similar concrete waterproofing products and shown the property retention in time (after 1-2 years of operation). Hydration products of the developed material were investigated using physicochemical research methods. It was shown that the component structure of the cement matrix creates the conditions for the synthesis of new hydration formations of C-S-H type, capable of concrete pore space calmatation. It was revealed that introducing the modifying complex additive of salts-electrolytes provides a directed formation of crystal-hydrate phases, capable of binding free portlandite in the concrete structure and filling voids and pores of the concrete. Concurrent administration of the natural zeolite additive promotes binding of free alkali and ensures forming of a durable waterproofing coating, which does not lose its insulating properties over time. Developed coatings become part of the concrete structure, sealing its composition and creating new stable formations, coatings are not peeled off over time and do not loosen the existing concrete as it was observed in the compared analogues. Thus, the developed method for restoring massive concrete structures allows to avoid costly removal and new concreting.